Deep history and deep listening: Indigenous knowledges and the narration of deep pasts. Issue 3 (3rd July 2021) - McGrath, Ann; Rademaker, Laura; Silverstein, Ben
ABSTRACT: This article outlines the possibilities of a deep history practice that engages with rather than sidelines Indigenous historical knowledges. Many Indigenous people insist that their knowledge of the deep past demands engagement. They do so, we suggest, because scientific historicism and Indigenous knowledge-systems and historicities already impinge upon and inform each other: they are intertwined. We propose 'deep listening' as a way historians might contribute to bringing these practices of deep history into more explicit conversation and address some of the challenges of doing so. Finally, we consider the example of the deep history of the Willandra Lakes in New South Wales Australia, revealing how this approach might allow for a more mutually satisfying deep history of the region.